RADAR TECHNIQUE FOR AIRCRAFT WITH AN ARTIFICIALLY REDUCED RCS UNDER CONDITIONS OF APPLICATION A RESONANT ELECTROMAGNETIC FIELD - PARKHOMEY, IGOR; BOIKO, JULIY (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The paper presents the results of a study of the radar technique for aircraft with an artificially reduced radar cross section (RCS) under the condition of using a resonant electromagnetic field. It is shown that the detection and tracking of air objects under conditions of artificially reduced RCS is carried out using radar information with resonant excitation of their radar absorbing coating. It is proposed to carry out tracking and detection of aircraft by a complex combination of an active radar channel with the formation of a resonant radio signal and a passive radar capable of receiving signals formed by an excited surface. It has been determined that by increasing the power level of the irradiating signal to 20-30%, it is possible to increase the area of the local conduction region of the dielectric by 10 times, which means that it will simplify the technical implementation of the method of locating aircraft. The proposed control methods make it possible to provide the necessary probability of detection accompanied by a radar target in a difficult jamming environment and thus increase the potential capabilities of the radar. In the course of the study, it was determined that the excitation and heating of the coating during enthalpy directly depends on the energy flux density of the electromagnetic microwave field per unit mass and area of the substance. It has been established that purposeful control of this effect makes it possible to substantiate the possibility of using enthalpy as a factor in excitation of air target coatings with an artificially reduced reflection area (RCS). The conditions for increasing the efficiency of radar targets with an artificially reduced RCS using a concentrated resonant electromagnetic field have been clarified. It is determined that the influence of such a field is accompanied by the concentration of the energy of the electromagnetic field in the crystal structure of the radio-absorbing coating of the aircraft due to the resonant irradiating signal, which causes temporary local conductivity and thermal radiation. Calculations of quantitative indicators characterizing the possibility of changing the electrically conductive properties of a carbon-type dielectric at a distance for the practical application of advanced radar systems are presented.